A uniform condominium statute for China based on a comparative study of the South African Sectional Titles Act and American Uniform Common Interest Ownership Act - Chen, Lei (Stellenbosch : Stellenbosch University, 2008)
Thesis (LLD (Private Law))--Stellenbosch University, 2008.